Ratio analysis as a tool in auditing / Abdul Rahman Mat Dali - Mat Dali, Abdul Rahman (1985)
The traditional audit approach places heavy reliance on standard audit programmes. These audit programmes were designed to test the internal control system of the client. The extent of testing depends on the assessment of the strength of the internal control.